2012
DOI: 10.7763/ijiet.2012.v2.206
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Classical Music as Background in the Story Video Comprehension Strategy among Students with Multiple Intelligence

Abstract: Music is the language of man's soul. It has an effect on the behavior and emotions of people of all ages. Music helps create a more positive school environment. Many students prefer to listen to music while studying because they believe it helps them to focus on their work. Hence, this study investigated the effectiveness of classical music as background in reading story video using headset in improving comprehension of students with multiple intelligence. In gathering the data, one section of the developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Dumont et al, (2017) believed exposure to music and music education could have a positive influence on child functioning. Silor (2012) developed students who read the stories and answered the comprehension examination with the use of classical music as background in the story video got higher scores compared to the result of students taking the comprehension test without the background of classical music.…”
Section: A Concept Of Readingmentioning
confidence: 98%
See 1 more Smart Citation
“…Dumont et al, (2017) believed exposure to music and music education could have a positive influence on child functioning. Silor (2012) developed students who read the stories and answered the comprehension examination with the use of classical music as background in the story video got higher scores compared to the result of students taking the comprehension test without the background of classical music.…”
Section: A Concept Of Readingmentioning
confidence: 98%
“…They found that music can positively motivate children's communication and learning functions. Silor (2012) also stated that students with multiple intelligence in music could effectively comprehend once their classical background music in the story video presentation with the use of headset while reading the story and analyzing the context. The researcher, White (2007) also implemented background music in the fourth-grade classroom at Logan Elementary School and proved that background music can be a useful tool.…”
Section: B Mean Scorementioning
confidence: 99%
“…Berk, 2008). Listening to music while studying is a preference for many students who think it helps them to concentrate on their work (Silor, 2012).…”
Section: Introductionmentioning
confidence: 99%